Jihad and death: the global appeal of Islamic State - Roy, Olivier (Comparative politics and international studies, 2017)
Intro -- Title Page -- Copyright Page -- Contents -- 1. Jihadism and Terrorism: The Pursuit of Death -- The New Forms of Terrorism and Jihadism -- When Jihadism Replaces Jihad -- Terrorism as Excommunication and Suicide -- The New Radicals -- 2. Who Are the Radicals? -- The Terrorists' Profile -- Friends, Brothers, and Wives -- Youth Culture, Delinquency, and Rebellion -- Born Again or Convert -- The Lack of "Objective" Causes -- The Connection with Middle East Conflicts -- 3. The Jihadi Imaginary: The Islamization of Radicalism -- What Role Does Islam Play in Radicalization? -- The Avenging Hero of the Suffering Muslim Community -- The Religion of Radicals: The Salafism Issue -- Youth Violence: Rebels in Search of a Cause -- 4. From the Shadow of Bin Laden to the Sun of ISIS -- The Myth of the "Third Generation" of Terrorists and the New Global Jihad -- The Irruption of ISIS in the Middle East -- Islamized Spaces, Tribal Spaces -- The Specific Logic of Middle East Geostrategy -- Conclusion: Waiting for Al-Godot -- Notes -- Bibliography -- Index.